2001
DOI: 10.1177/107110070102200908
|View full text |Cite
|
Sign up to set email alerts
|

Tibiotalocalcaneal Arthrodesis: A Biomechanical Analysis of the Rotational Stability of the Biomet Ankle Arthrodesis Nail

Abstract: We hypothesized that the posterior-to-anterior (PA) calcaneal interlocking screw of the Biomet Ankle Arthrodesis Nail would increase rotational stability secondary to increased bone purchase compared with the standard lateral-to-medial (transverse) screw. Each of 10 fresh human cadaver lower limbs (five matched pairs) were stabilized with a nail inserted retrograde through the calcaneus, talus, and tibia according to standard technique. One limb of each pair was fixed with a transverse calcaneal screw; the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…Intracalcaneal fixation has been shown to be an important factor affecting stability [18,20,27]. Mann et al concluded that the posterior-to-anterior routing of a calcaneal locking screw significantly enhances stability [18]. Muckley et al demonstrated the superiority of angle-stable over non-anglestable intracalcaneal locking [20].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Intracalcaneal fixation has been shown to be an important factor affecting stability [18,20,27]. Mann et al concluded that the posterior-to-anterior routing of a calcaneal locking screw significantly enhances stability [18]. Muckley et al demonstrated the superiority of angle-stable over non-anglestable intracalcaneal locking [20].…”
Section: Discussionmentioning
confidence: 97%
“…Many of the patients considered for TTCA have multiple comorbidities affecting bony stability [6][7][8]27]. Intracalcaneal fixation has been shown to be an important factor affecting stability [18,20,27]. Mann et al concluded that the posterior-to-anterior routing of a calcaneal locking screw significantly enhances stability [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to biomechanical stability, factors that may contribute to successful outcomes after TTC arthrodesis include maintenance of anatomic alignment, techniques that are easily reproducible, and preservation of surrounding soft tissues and blood supply (2,7) . Unfortunately, nonunion rates of 15% and higher have been reported in the literature following TTC arthrodesis (2,8) .…”
Section: Introductionmentioning
confidence: 99%
“…A critical factor when performing these types of salvage procedures is achieving stable fixation with compression of the subtalar and ankle joint (8) . There are many described fixation methods for performing the TTC arthrodesis, including crossed compression screws, intramedullary (IM) fixation, blade plate and locking plates (1,(7)(8)(9)(10) . However, the use of lateral locking plate for TTC fusion has not been described with a specific plate design that conforms to the lateral portion of the tibiotalocalcaneal surface.…”
Section: Introductionmentioning
confidence: 99%